On the automorphism group of token graphs of complete bipartite graphs - Fabila-Monroy, Ruy; Trujillo-Negrete, Ana (Boletín de la Sociedad Matemática Mexicana, 2025)
Let G be a graph of order n and let k∈{1,2,…,n-1}. The k-token graph of G is the graph, Fk(G), whose vertices are all the k-subsets of vertices of G, where two such k-sets are adjacent whenever their symmetric difference is an edge of G. In this paper, we determine the automorphism group of the k-token graph of the complete bipartite graph Km,n.